CORRECTION OF POISTURE DISORDERS AMONG HARD OF HEARING ATHLETES BY MEANS OF ADAPTIVE PHYSICAL TRAINING IN THE TRAINING PROCESS - Zoya Sapronova; Arsen Abdullayev (Вестник Северо-Кавказского федерального университета)
Correction ofposture disorders among deaf and hard of hearing adolescents is increasinglybecoming of health-pedagogical and social importance. Objective of the research: to develop and validate the effectiveness of methods of correcting postural disorders among athletes with deprivation of hearing at the age of 14-15 years old, during the training process. Together with the doctors of Stavropol Regional Center of Physical Therapy and Sports Medicine we have carried out visual, anthroposcopic, palpation and anthropometric surveys with analysis of complaints and anamnesis data of hard of hearing athletes involved in track andfield athletics at the age of 14-15 years old. For the correction of posture among athletes deprived of hearing it a targeted experimental method of the use of special means of adaptive physical training to correct «round back» was developed and implemented on the basis of modern scientific understanding of the mechanisms ofmotor regulation, structure-function relationships in the musculoskeletal system. Teaching experiment among athletes with hearing deprivation included four successive steps aimed at creating a posture and strengthening of the power of the upper body muscles, abdominal muscles and spinal mobility.